The Dilemma of Tourism Moral Economy and the Turismo delle Radici: Reflections on the Italian Diaspora in Brazil and Experiences of the Italianità as Authenticity - Fazito de Almeida Rezende, Dimitri (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
Roots tourism is noteworthy for a strong emotional bond between the tourist and the “place of destination” even before the trip takes place. It is also important to point out that the roots tourism is related to the mobility regime of diaspora, qualifying the so-called “diasporic tourism” and many other markers of mobility related to genealogical and affective ties with an original community. It can be assumed that the roots tourism (specifically the Turismo dell Radici – TdR) is a type of mobility and tourism practice integrated broadly in a social system of multiple space-time scales (the regime mobility across the globe). We believe that TdR can be understood as an analytically privileged sociological phenomenon, since it is a regular fact that is increasingly widespread in the liquid modernity, contributing in a decisive way to think about the mobile lives of contemporary tourism and its embeddedness in a globalised regime of mobilities. In this study we seek to investigate the sociological “mechanisms” that characterize the tourist experiences of TdR through an exploratory case study about the relation of the tourism experiences and the consolidation of the Italian diaspora community settled in Brazil. First, we organized the text with the conceptual problematization of the TdR and its consequences for our understanding of the phenomenon of tourist practices and the constitution of communities and identities affected by the regime of mobilities across the globe (the formation of a transnational community and a very particular identity – the representation of the “Italianity”). In a second part, we discuss the TdR and the debate on authenticity and the performance in the tourism space, highlighting the importance of understanding the interaction between people, places, goods, services, scales and distances under the framing of a “tension” provoked by the new moral economy in Modernity. The persistent reflections on the TdR tend to put a relational bias in the sense of focusing on the point of view of the “origin”, assumed in the analyses as a fixed and homogeneous territory of “return”. However, TdR should not focus only on the perspective of the “original place”, real or imaginary. Another analysis must be attempted, considering the relational and re-dimensioned aspect of territorial scales according to the historical processes that interconnect origin and destination, local and global, constructed and imagined space, hot and cold. To this end, we planned an exploratory case study related to the formation of the Italian diaspora communities in Brazil and the accelerated growth of projects characterized as Turismo delle Radici connecting both local associations (of transnationalised identities) founded in Brazilian territory to their original communities in the Italian peninsula (comuni and regione). We highlight the social mechanisms of this moral economy that implies roots tourism as a vector of the Italianità – Italianity – that generates self-sustainability at different levels (local-global) balancing authentic experience out of the massive tourism industry. We suggest that associationism contributes for strong ties among Italian communities and exert a decisive role in the promotion of tourist experiences of "return" in a transnational social field. Then, travelling experiences in the place of destination strengthen the sense of “atemporal” belonging, the Italianità feeling that protects one against overtourism while simultaneously preserving the moral field of dense ties and transactions to homeland. Methodologically, the case study of the Italian diaspora in Brazil and the formation of the sense of belonging as Italianity makes it possible to problematize the phenomenon of TdR through the paradoxes of the authenticity of tourism practices in the moral economy of the globalised world.